Ion-induced modification of structural, optical and luminescence behaviour of Gd2MoO6 nanomaterials: A comparative approach. (June 2016) - Dutta, S.; Sharma, S.K.; Kumar, Vijay; Som, S.; Swart, H.C.; Visser, H.G.
Abstract: The recent study reports the effects of swift heavy ion (SHI) on the structural, optical and luminescence behaviour of a hydrothermally synthesized Gd2 MoO6 nanomaterial irradiated via three different ions (30 MeV Li 3+, 75 MeV C 6+, and 100 MeV Ag 7+ ) at various energy and fluence. The pristine and ion-irradiated samples were studied by X-ray diffraction (XRD) pattern, field emission scanning electron microscopy (FESEM) images, diffuse reflectance (DR) spectroscopy, photoluminescence (PL) and thermoluminescence (TL) spectroscopy techniques. The XRD studies and the FESEM results reveal the loss of crystallinity and decrease of the particle size after SHI irradiations. DR spectra exhibit a shift in the absorption band towards the higher wavelength region after ions irradiation, reflecting in a reduction in the band gap. After ion irradiation the intensity of the PL peaks decreased but the band position remained the same. The TL characteristics were investigated in detail, and the trapping parameters of the ion irradiated material were determined via the glow curve interpretation method. The results can be correlated with linear energy transfer of the irradiated ions by using the SRIM code for the irradiated ions. Highlights: Gd2 MoO6 nanomaterials were synthesized via hydrothermal method. The as synthesized phosphors were irradiated by different swift heavy ion. Ion induced structural and luminescence modifications were reported. The results can be correlated with linear energy transfer of the irradiated ions.